(Retracted Article) THE DEVELOPMENT OF A TEACHING MODEL BASED ON CONSTEUCTIVISM THEORY TO ENCHANCE THE SCIENTIFIC CONCEPTS OF GEADE 12 UNDER THE JURISDICTION OF NAKHON SI THAMMARAT MUNICIPALITY - Noppon, Supawadee (Journal of Social Science and Cultural, 2023)
This objectives of this research are to 1. Study and analyze data to develop learning and teaching. 2. To develop and direct the use of learning and teaching formats. 3. To try the use of learning and teaching formats. 4. Study student’s opinions on learning and teaching according to learning and teaching formats. The result of the research concluded that 1) Basic data for developing learning and teaching models to enhance scientific concepts is that teaching and learning must rely on prior knowledge as a base for learning new things. Through a learning process that interacts with friends and teachers. Create by yourself knowledge and can share knowledge with others. There is an examination of own knowledge and understanding with teachers as facilitators. 2) A learning and teaching format based on constructivism theory to enhance concept the scientific concepts of students of Grade 12 under the jurisdiction of Nakhon Si Thammarat Municipality consists of 6 elements and a 5 - step learning and teaching process as follows: 2.1) Principles 2.2) Objectives 2.3) The learning and teaching process consists of 2.3.1) Verifying Knowledge 2.3.2) Instructing Fundament Knowledge and skill 2.3.3) Constructing Concepts 2.3.4) Sharing knowledge 2.3.5) Assessing Knowledge and Understanding 2.4) Knowledge content 2.5) Conditions for using the teaching model, consisting of 2.5.1) the role of the student 2.5.2) the role of the teacher 2.6) measurement of evaluation. 3) Students' scientific conceptions after studying according to learning and teaching formats constructivism theory were significantly higher than before studying at the .05* level. 4) Students agree with the learning and teaching process according to the learning and teaching format according to constructivism theory at the highest level.